Workshop Pemberdayaan Ibu PKK dan Karang Taruna melalui Pembuatan Kerajinan Bunga dari Kawat Bulu - Romli; Meri Octaviani; Nailah Alilatul Bariza; Ayu Rizka Amanda; Alya Karinisa Danikenp; Iin Muslimah; Arya Bharata Sena; Noval Pabriyansya Winata (PT Cendekia Education Center, 2026)
This community service activity aimed to empower members of PKK (Family Welfare Empowerment) and Karang Taruna in Desa Petanang, Lembak District, Muara Enim Regency through a workshop on making flower crafts from pipe cleaners. The activity was conducted on January 26, 2026, involving approximately 35 participants consisting of 15 PKK members and 20 youth and community members. The method used was participatory training and mentoring, including planning, implementation, and evaluation stages. Participants received introductory material on creative economy concepts followed by demonstrations and hands-on practice in creating sunflower, aster, and lavender crafts. The results showed that most participants were able to independently produce at least one flower craft with satisfactory quality. The workshop not only improved participants’ technical skills and creativity but also strengthened social collaboration between women and youth groups. Furthermore, the activity fostered entrepreneurial motivation and opened opportunities for developing home-based micro-enterprises. Therefore, the workshop contributed positively to enhancing community capacity and supporting sustainable village economic empowerment.